Stone observatory at Bric Pinarella (Finale Ligure, Italy) - Codebo, M.; De Santis, H.; Pesce, G.L. (Archaeoastronomy and Ancient Technologies, 2017)
This paper reports the latest findings on the stone observatory of Bric Pinarella (Finale Ligure, Savona, northern Italy), first described in 2006 at the conference of the Italian Society of Archaeoastronomy (SIA). The settlement is located near the upland plain of the Manie, which is an area known for the archaeological remains and the natural attractions. The settlement is constituted of three archaeological evidences: a small building, two short standing stones 44 centimetres apart, and a standing stone vertically fitted in the ground with a natural hole in its free end. Archeoastronomical investigations demonstrated that the hole in the standing stone allows positioning of the sunrise at the equinoxes over the Manie skyline, whereas the two standing stones allow tracing of the local meridian with azimuth 360-180. Other possible astronomical functions such as the identification of the elongation of the Sun from the east cardinal point and the study of the Sun and Moon's upper meridian transit (in this respect the site could be described as a rudimentary meridian circle) are discussed in the paper. Despite the fact that, to date, its construction time is still unknown, the most recent findings show that the whole site could be an old astronomical observatory.